APLIKASI SMARTDIET MENGGUNAKAN LOGIKA FUZZY BERBASIS ANDROID - Feri Candra (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Abstract Health is an essential thing in our lives. One of the characteristics of a healthy body is having an ideal body. To get an ideal body, we should regulate our diet or eating pattern to our daily activity. We can find out that our body is ideal or not by using BMI formula. Moreover, we can total our daily calories need by using BMR formula. Both of the formulas actually can be calculated manually, but the methods are not efficient. Also, in those formulas, the calculations are still standard and inflexible. Therefore, this study uses fuzzy logic with Mamdani methods to calculate the body mass index and calorie requirement figures. Using the fuzzy logic can give tolerances to the result so that there are no significant results. This application uses Java language based on Android so that it can be used practically on smartphones. The result shows that BMI and BMR obtained by this application are the accuracy of 89.62% and the error value of 10.38%.